Fenomena Judi Online Higgs Domino Dikalangan Mahasiswa Pada Masa Pandemi Covid-19 di Kota Tanjungpinang - Resky Supratama; Marisa Elsera; Emmy Solina (Jayapangus Press, 2022)
Gambling is a societal disease that affects all levels of society, including students in Tanjungpinang City. In the midst of a pandemic, all systems of people's lives have changed from offline to online, including in this research the gambling that hit students in Tanjungpinang City. This study aims to find out what causes the Higgs Domino online gambling game to occur in the midst of a pandemic in the Tanjungpinang City Student environment. The method used in this research is qualitative method. The data obtained through the results of semi-structured in-depth interviews based on interview guidelines and the development of questions, observations, participation and documentation. In research to determine informants using the Purposive Sampling Technique or first determine the criteria of the informants. Based on the results of the analysis, researchers found the phenomenon of the widespread use or game of online gambling games Higgs Domino among students in the city of Tanjungpinang caused by social environmental factors, this is evidenced by the results of interviews which can be concluded that Higgs Domino players first learned about this game from friends, and the existence of Intense communication and interaction between players, starting from sharing information about how to access this game or download it, how to play, how to buy and sell chips. As stated by the Differential Association theory, Edwin H. Shutterland, Sutherland argued that criminal behavior is a behavior that can be understood and also studied in the social environment of society.